Strategies for Improving Teacher Service Quality Through Strengthening Organizational Citizenship Behavior (OCB), Interpersonal Communication, Organizational Climate, and Work Motivation - Deden Iskandar; Didik Notosudjono; Rais Hidayat (International Journal of Technology and Education Research, 2025)
This study aims to formulate effective strategies for improving teacher service quality through a multi-factor approach, namely Organizational Citizenship Behavior (OCB), interpersonal communication, organizational climate, and work motivation. Teacher service quality is an important indicator in the continuous improvement of education quality. The research method used is a quantitative approach with an explanatory causal design. Data were collected through questionnaires administered to teachers from various educational levels and analyzed using path analysis techniques. The results of the study indicate that OCB, interpersonal communication, organizational climate, and work motivation significantly and simultaneously influence the improvement of teacher service quality. OCB acts as a mediating factor that strengthens the influence of other variables on service quality. The practical implications of these findings highlight the importance of strengthening organizational culture, interpersonal communication training, and reward and motivation systems to promote teacher professionalism. An integrative strategy based on strengthening organizational behavior and a humanistic approach is recommended as a model for improving teacher service quality in the Indonesian educational context.